2019
DOI: 10.1111/bjd.17789
|View full text |Cite
|
Sign up to set email alerts
|

Serum cytokeratin 19 fragment 21‐1 and carcinoembryonic antigen combination assay as a biomarker of tumour progression and treatment response in extramammary Paget disease

Abstract: Summary Background Extramammary Paget disease (EMPD) is a rare intraepithelial adenocarcinoma affecting the genitals and axillary regions. As metastasis of these tumours is itself rare, solid disease management strategies have not been established. Serum carcinoembryonic antigen (CEA) and cytokeratin 19 fragment 21‐1 (CYFRA 21‐1) levels have been identified as candidate biomarkers for tumour progression in EMPD. Objectives To determine the accuracy of and the correlation between these markers in patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Studies of CYFRA expression levels in EMPD by Nakamura et al . provide further diagnostic information reporting no elevation in serum CYFRA levels or CEA in patients with primary invasive EMPD, but a significant increase of both markers in patients with evidence of nodal and distant organ metastatic progression . Collectively, the reports by Mijiddorj et al .…”
mentioning
confidence: 69%
See 3 more Smart Citations
“…Studies of CYFRA expression levels in EMPD by Nakamura et al . provide further diagnostic information reporting no elevation in serum CYFRA levels or CEA in patients with primary invasive EMPD, but a significant increase of both markers in patients with evidence of nodal and distant organ metastatic progression . Collectively, the reports by Mijiddorj et al .…”
mentioning
confidence: 69%
“…In the current issue of the BJD , two studies highlight potential biomarkers for EMPD; levels of serum cell‐free (cf)DNA) and a combination of serum cytokeratin 19 fragment 21‐1 (CYFRA) and serum carcinoembryonic antigen (CEA) . cfDNA is currently being studied in a range of fields from prenatal diagnosis of trisomy disorders, to its role as a diagnostic, prognostic and predictive biomarker in a host of cancer settings and refers to all nonencapsulated DNA in the bloodstream.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The findings of the present study demonstrated that the combination of CEA and CYFRA levels had higher sensitivity for detecting LN metastasis of extramammary Paget’s disease than each of the other biomarkers evaluated alone. While this study was under review process, a similar study was published 11 . The differences between the two studies were the target (lesion) of the tumor and the validation of multiple tumor markers.…”
Section: Discussionmentioning
confidence: 99%